Analisis Debt to Asset Ratio dan Current Ratio Dalam Menilai Return On Asset Pada PT. Ultrajaya Milk Industri Tbk yang terdaftar di BEI Periode Tahun 2016 – 2020 - Nurul Fitria; Edison Hamid; Rachmawati (PARAMETER, 2022)
This study aims to determine how the Debt to Asset Ratio (DAR) and Current Ratio (CR) in assessing the Return On Assets (ROA) the object of research is PT. Ultrajaya Milk Industry, Tbk, the data is taken from the financial statements for the period 2016-2020. This research uses descriptive qualitative method which consists of three variables, namely the debt to asset ratio (DAR) and current ratio (CR) as independent variables and return on assets (ROA) as the dependent variable. Data analysis used case studies (non-hypothesis). Based on the results of data analysis, it shows that the average debt to asset ratio (DAR) per year as a whole is 22%, this condition is in the very good category based on industry average standards. For the average current ratio (CR) per year of 406%, this condition is in the very good category based on industry average standards. Then from the results of the weighting of the debt to asset ratio (DAR) in assessing the average return on assets (ROA) for the last 5 years, namely the 2016-2020 period, it contributed 0,79%. Next from the results of the weighting of the current ratio (CR) in assessing the average return on assets (ROA) for the last 5 years, namely the 2016-2020 period, it contributed 0,04%. Then from the results of the weighting of the debt to asset ratio (DAR) and current ratio (CR) in assessing the average return on assets (ROA) for the last 5 years, namely the 2016-2020 period, it contributed 0,83% and the rest was contributed by other factors not examined. in this research. Abstrak Penelitian ini bertujuan untuk mengetahui bagaima Debt to Asset Ratio (DAR) dan Current Ratio (CR) dalam menilai Return On Assets (ROA) obyek penelitian adalah PT. Ultrajaya Milk Industri, Tbk, data diambil dari laporan keuangan periode tahun 2016-2020. Penelitian ini menggunakan metode kualitatif diskriptif yang terdiri dari tiga variabel yaitu Debt to Asset Ratio (DAR) dan current ratio (CR) sebagai variabel independen dan return on assets (ROA) sebagai variabel dependen. Analisis data yang digunakan studi kasus (non hypotesis). Berdasarkan hasil analisis data menunjukkan bahwa rata-rata Debt to Asset Ratio (DAR) per tahun secara keseluruhan sebesar 22% kondisi ini masuk dalam katagori sangat baik berdasarkan standar rata-rata industri. Untuk rata-rata current ratio (CR) pertahun sebesar 406% kondisi ini masuk dalam katagori sangat baik berdasarkan standar rata-rata industri. Lalu dari hasil pembobotan debt to asset ratio (DAR) dalam menilai return on assets (ROA) rata-rata 5 tahun terakhir yaitu periode tahun 2016-2020 berkontribusi sebesar 0,79%. Selanjutnya dari hasil pembobotan current ratio (CR) dalam menilai return on assets (ROA) rata-rata 5 tahun terakhir yaitu periode tahun 2016-2020 berkontribusi sebesar 0,04%. Kemudian dari hasil pembobotan debt to asset ratio (DAR) dan current ratio (CR) dalam menilai return on assets (ROA) rata-rata 5 tahun terakhir yaitu periode tahun 2016-2020 berkontribusi sebesar 0,83% dan sisanya dikontribusi oleh faktor-faktor lain yang tidak diteliti dalam penelitian ini.